2007
DOI: 10.1111/j.1468-0432.2007.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Pacifying an Aggressive Client: ‘Feminine’ Skills and Preventing Violence in Caring Work

Abstract: This article explores the complex interconnection between gender and emotion in the context of client-perpetrated violence at work, focusing on interviews with and writings by Finnish nurses and social workers to discuss the 'feminine' emotional skills that are supposed to prevent violence. The social formation of these skills is analysed with the concept 'emotional habitus': emotional skills derive from the socially acquired disposition to manage emotions according to the gendered values of caring work. Emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
25

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 15 publications
2
40
0
25
Order By: Relevance
“…In this way, they drew on interpersonal skills and emotional labour to retreat from the encounter without aggravating the customer, or rather by pacifying the customer. Previous research has documented the emotional labour employees use to pacify violent customers, highlighting the gendered nature of this interaction (Baines, 2004; Baines and Cunningham, ; Virkki, ). This research has also found that the interpersonal skills that employees use are often developed tacitly by watching colleagues or through repeated experience (Virkki, ).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, they drew on interpersonal skills and emotional labour to retreat from the encounter without aggravating the customer, or rather by pacifying the customer. Previous research has documented the emotional labour employees use to pacify violent customers, highlighting the gendered nature of this interaction (Baines, 2004; Baines and Cunningham, ; Virkki, ). This research has also found that the interpersonal skills that employees use are often developed tacitly by watching colleagues or through repeated experience (Virkki, ).…”
Section: Resultsmentioning
confidence: 99%
“…2005; Ryan & Bowers 2005), but there were also studies conducted in Sweden (Carlsson et al . 2000) and Finland (Virkki 2008). Table 2 provides a summary of the major findings of each study.…”
Section: Resultsmentioning
confidence: 99%
“…They express genuine concern for the patient, appear non‐threatening and have a permissive, non‐authoritarian manner (Carlsson et al . 2000; Duperouzel 2008; Gertz 1980; Johnson & Hauser 2001; Lane 1986, Virkki 2008). These qualities help to gain the patient's trust, making appeals for self‐control more likely to be accepted (Duperouzel 2008; Lowe 1992).…”
Section: Resultsmentioning
confidence: 99%
“…As indicated in the examples given, room attendants as front‐line service employees are expected to have competencies in ‘sophisticated social intelligence’ so as to deter the guest without giving offence (Harris, , p. 146). Some employees, frequently the older ones, deployed humour to deal with and pacify difficult customers, thus reproducing the gendered attributes of subordination (Virkki, ). In this way the socio‐cultural model within attendants' workplaces enabled sexual harassment to operate as a mechanism to maintain male dominance (Bedford and Hwang, ; O'Hare and O'Donohue, ).…”
Section: Hotel Workplace Culturementioning
confidence: 99%